2006
DOI: 10.1111/j.1365-2222.2006.02551.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of interferon‐γ and interferon regulatory factor 1 polymorphisms with asthma in a family‐based association study in Taiwan

Abstract: These findings provide strong evidence of which IFN-gamma CA repeat and IRF-1 GT repeat polymorphisms influence the risk of asthma for children in Taiwan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 36 publications
2
12
1
Order By: Relevance
“…In the Guangdong Pearl River Delta region, the results show that the CA repeat sequence was repeated 11-18 times (i.e., alleles CA 11 -CA 18 ), as determined by capillary electrophoresis. This was different from other reports wherein 12-18 repetitions were found among the Taiwanese population (Wang et al, 2006) and 10-18 times among Indians (Nagarkatti et al, 2002). In the present study, the genotypic frequency distributions of CA 12 + CA 12 + , CA 12 + CA 12 − and CA 12 − CA 12 − were compared with those in the asthmatic group and the control group and no correlation was found between the frequency and asthma susceptibility.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…In the Guangdong Pearl River Delta region, the results show that the CA repeat sequence was repeated 11-18 times (i.e., alleles CA 11 -CA 18 ), as determined by capillary electrophoresis. This was different from other reports wherein 12-18 repetitions were found among the Taiwanese population (Wang et al, 2006) and 10-18 times among Indians (Nagarkatti et al, 2002). In the present study, the genotypic frequency distributions of CA 12 + CA 12 + , CA 12 + CA 12 − and CA 12 − CA 12 − were compared with those in the asthmatic group and the control group and no correlation was found between the frequency and asthma susceptibility.…”
Section: Discussioncontrasting
confidence: 81%
“…In the present study, the genotypic frequency distributions of CA 12 + CA 12 + , CA 12 + CA 12 − and CA 12 − CA 12 − were compared with those in the asthmatic group and the control group and no correlation was found between the frequency and asthma susceptibility. This observation is consistent with the results by Kumar and Ghosh (2008), but is contradictory with the results obtained from the Taiwan population (Wang et al, 2006) and that in India (Nagarkatti et al, 2002) wherein the correlation between genotypic frequency and asthma was reported. The disagreement might be related to the differences in ethnicity, region, and research methods among the different studies.…”
Section: Discussionsupporting
confidence: 77%
“…IRF-1 is an early response gene involved in a diverse set of transcriptional regulatory processes (21,25). Interestingly, a strong association was found between IRF-1 polymorphism and childhood atopic asthma (46,47). Further, mortality associated with injection of a lethal dose of lipopolysaccharide was significantly reduced in IRF-1 knockout mice (48).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, genetic variants in PLAU have been reported to associate with asthma and with airway hyperresponsiveness [27]. Further, multiple studies have indicated the role of IRF1 , interferon regulator factor 1, in asthma risk in several ethnicities [2832]. As a proof of concept, our work followed up on IRF1 , however, all other genes could be further examined as peripheral gene expression changes markers for GC sensitivity.…”
Section: Discussionmentioning
confidence: 97%